A poisonous surprise under the coat of the African crested rat. - Kingdon, J; Agwanda, B; Kinnaird, M; O'Brien, T; Holland, C; Gheysens, T; Boulet-Audet, M; Vollrath, F (2012)
Plant toxins are sequestered by many animals and the toxicity is frequently advertised by aposematic displays to deter potential predators. Such 'unpalatability by appropriation' is common in many invertebrate groups and also found in a few vertebrate groups. However, potentially lethal toxicity by acquisition has so far never been reported for a placental mammal. Here, we describe complex morphological structures and behaviours whereby the African crested rat, Lophiomys imhausi, acquires, dispenses and advertises deterrent toxin. Roots and bark of Acokanthera schimperi (Apocynaceae) trees are gnawed, masticated and slavered onto highly specialized hairs that wick up the compound, to be delivered whenever the animal is bitten or mouthed by a predator. The poison is a cardenolide, closely resembling ouabain, one of the active components in a traditional African arrow poison long celebrated for its power to kill elephants.